The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0168995
|View full text |Cite
|
Sign up to set email alerts
|

Collective Behaviour in Video Viewing: A Thermodynamic Analysis of Gaze Position

Abstract: Videos and commercials produced for large audiences can elicit mixed opinions. We wondered whether this diversity is also reflected in the way individuals watch the videos. To answer this question, we presented 65 commercials with high production value to 25 individuals while recording their eye movements, and asked them to provide preference ratings for each video. We find that gaze positions for the most popular videos are highly correlated. To explain the correlations of eye movements, we model them as “int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…In particular, we confirmed a positive association between fixation map consistency and scene memorability in both datasets (Fig. 3), consistent with previous research with static scenes (Khosla et al, 2015;Mancas & Le Meur, 2013) and videos (Burleson-Lesser et al, 2017;Christoforou et al, 2015). Moreover, the observed correlation values between fixation map consistency and scene memorability from the Edinburgh and FIGRIM datasets (0.25 [0.08,0.40] and 0.22 [0.14, 0.29], respectively) were very similar to the values reported by Khosla et al…”
Section: Discussionsupporting
confidence: 92%
“…In particular, we confirmed a positive association between fixation map consistency and scene memorability in both datasets (Fig. 3), consistent with previous research with static scenes (Khosla et al, 2015;Mancas & Le Meur, 2013) and videos (Burleson-Lesser et al, 2017;Christoforou et al, 2015). Moreover, the observed correlation values between fixation map consistency and scene memorability from the Edinburgh and FIGRIM datasets (0.25 [0.08,0.40] and 0.22 [0.14, 0.29], respectively) were very similar to the values reported by Khosla et al…”
Section: Discussionsupporting
confidence: 92%
“…With these two constraints determined by the data, we really only have 3 degrees of freedom remaining for optimization. Parameter µ n is directly specified by µ z (15). Parameters σ a and σ 2 n will be reduced to a single parameter, namely, the logarithm of the signal to noise ratio:…”
Section: Attention Modelmentioning
confidence: 99%
“…Previous studies have shown that eye movements are correlated across subjects during video presentation [11,12]. This inter-subject correlation (ISC) of eye-movements is elevated for dynamic, well-produced movies and video advertising [13][14][15], and is affected by the viewing task [16]. A variety of eye tracking measures have been used in educational research [17].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the end water of the Han River was used as the water source, and 110 species and 102 species of organic matter were detected in the wet and dry periods, respectively. Burlesonlesser et al [6] performs photocatalytic degradation of toxic and harmful organic wastewater by TiO 2 photocatalytic degradation, seawater desalination pretreatment and seafloor manganese nodules on organic pollutants. The research results provide valuable scientific theoretical basis and reference for industrial application in photocatalysis.…”
Section: State Of the Artmentioning
confidence: 99%